2003
DOI: 10.1152/ajpregu.00339.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic activity and the underlying action potentials in sympathetic nerves: a simulation

Abstract: Understanding the relationship between activity recorded in sympathetic nerves and the action potentials of the axons that contribute to that activity is important for understanding the processing of sympathetic activity by the central nervous system. Because this relationship cannot be determined experimentally and is difficult to predict analytically, we simulated the summed action potentials of 300 axons. This simulation closely resembled actual sympathetic activity and permitted us to know how many action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Beat‐to‐beat separation of sympathetic bursts theoretically becomes unclear as heart rate increases and it may therefore be desirable in future experiments to incorporate shorter time constants for integration of the nerve signal (for example, 0.04 s). It should also be noted that the shape of our fused bursts are remarkably similar to those predicted by a mathematical simulation showing a direct linear relationship between the number of action potentials contributing to a burst and the resulting burst amplitude (Tang et al 2003). We did not record activity from single fibres, and so we cannot confirm or refute this notion.…”
Section: Discussionsupporting
confidence: 79%
“…Beat‐to‐beat separation of sympathetic bursts theoretically becomes unclear as heart rate increases and it may therefore be desirable in future experiments to incorporate shorter time constants for integration of the nerve signal (for example, 0.04 s). It should also be noted that the shape of our fused bursts are remarkably similar to those predicted by a mathematical simulation showing a direct linear relationship between the number of action potentials contributing to a burst and the resulting burst amplitude (Tang et al 2003). We did not record activity from single fibres, and so we cannot confirm or refute this notion.…”
Section: Discussionsupporting
confidence: 79%
“…An important finding is that control, resting AP was located 5-6 mmHg above AP at midrange, considering either mean RSNA level or RSNA total power. Overall, these observations indicate that the mean level and the total power basically provide the same information regarding the baroreflex control of RSNA (33).…”
Section: Discussionmentioning
confidence: 56%
“…To circumvent this difficulty, Zhang & Johns (1998) reduced the high dimension of the RSNA signal to a simpler form by subjecting the filtered and rectified signal to cluster analysis (Malpas & Ninomiya, 1992). From the resultant smoother waves of activity, they measured peak‐to‐peak intervals which, according to Tang et al (2003), are likely to provided a fair indication of frequency of action potential traffic. Zhang & Johns (1998) showed that an increase in RSNA, induced reflexly by stimulating a brachial nerve bundle, resulted in a decrease in the value of the largest Lyapunov exponent and in the correlation dimension, suggesting that there was less chaos.…”
Section: Discussionmentioning
confidence: 99%